GAMBARAN KEJADIAN COVID-19 DI WILAYAH KERJA PUSKESMAS UMBULHARJO I (PERIODE BULAN MEI – AGUSTUS 2021) - Rokhmayanti Rokhmayanti; Titim Martini; Ike Lukita Padmawati; Fardhiasih Dwi Astuti; Siti Kurnia Widi Hastuti (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
COVID-19 cases since the beginning of 2020 have experienced a fluctuating increase. This incident is caused by a virus that can attack everyone with a high level of transmission. Characteristics of events in each region may be different. Therefore, knowing the distribution of epidemiology in an area is important to study. The purpose of this study was to determine the epidemiological description based on people, place, and time in the working area of the Umbulharjo I Health Center. This study used an analytical descriptive method with secondary data sources derived from the results of an epidemiological investigation conducted in May – August 2021. The results of this study indicate that the majority of COVID-19 cases in the working area of the Umbulharjo I Health Center are women, aged 26-35 years, with the highest area in Kelurahan 3 which has a higher population density than other areas, and the highest spike in cases occurred in The month of July with the most daily cases occurred on 28-29 June 2021.